Verbal communication: an essential factor in international trade - Ribeiro, Sandra (2020)
Establishing a business relationship is a complex action influenced by different variables. When we approach the international context, the complexity becomes even greater, with communication between commercial actors playing a crucial role. In this sense, the promotion of effective and unimpeded verbal communication between international partners is crucial for the success of any transaction. It is in this context that economics of language gains relevance, allowing the inclusion of the language spoken by the commercial partners as one of the explanatory factors of international trade, assuming in the explanatory gravitational models of trade flows between countries the role of facilitator of trade exchanges or, on the contrary, of an obstacle to the commercial relationship. Studies in the area of economics of language reveal that economic relations are strongly influenced by language, but language choices can also be influenced by economic factors, which is why this is a bilateral relationship. The study we present here focuses on how verbal communication (measured according to linguistic proximity, that is, a greater or lesser degree of similarity between the language spoken by two business partners) influences the commercial relations established in an international context. In this study, we conclude that, based on data on the volume of Portuguese exports in 2015, the ease of verbal communication with the trading partner has a positive influence on the increase in trade - in empirical terms, this conclusion is corroborated by the fact that Spain is Portugal's main trading partner. We conclude that the language factor is not being well used by the Portuguese State, as the linguistic proximity could be used to increase Portuguese exports, namely with the countries that compose the Community of Portuguese Speaking Countries (CPLP) and with those that integrate the Southern Common Market (Mercosur).